Reorientasi Kerja Sama Pembangunan Internasional Indonesia (Studi People-Centered Development pada Strategi Indonesian Aid di Kenya) - Dinda Salsabila Putri; Widyastari, Zahrani (Department of International Relations, Brawijaya University, 2026)
International development cooperation between Indonesia and Kenya through Indonesian Aid reflects Indonesia’s transition from aid recipient to emerging donor within the South-South Cooperation framework. Although Indonesian Aid formally adopts People-Centered Development (PCD) principles, its implementation remains largely state-centric, limiting substantive community participation and local ownership. Using a qualitative literature-based approach, this study assesses participation, empowerment, sustainability, and cultural relevance within health and family planning programs in Kenya. The findings reveal a structural ambiguity between empowerment-oriented development discourse and the institutional realities of state-driven diplomacy. While participatory elements are present at the implementation stage, strategic planning and decision-making remain predominantly mediated through intergovernmental mechanisms. This imbalance generates a gap between Indonesia’s diplomatic positioning and Kenya’s localized development needs. The study argues that without greater transparency, institutional decentralization, and stronger community control over program processes, People-Centered Development risks becoming instrumental rather than transformational. This research introduces the concept of state-mediated People-Centered Development to explain the structural tension between empowerment discourse and state-driven diplomacy, contributing to the literature on emerging donors and South-South Cooperation.